Capital Structure Analysis of Haryana State Cooperative Supply and Marketing Federation (HAFED) - Kaur, Jasmeet; Dhaliwal, Navkiranjit Kaur (Gyan Management Journal, 2013)
Capital structure determines how a firm finances its overall operations and growth by using different sources of funds. Capital structure planning is very important for the survival of business in the long run. The cooperative marketing federations like HA FED are playing an important role in agricultural marketing at state levels and undertake various activities which require having proper arrangement and management of funds. The present paper attempts to analyse the capital structure of Haryana State Cooperative Supply and Marketing Federation (HA FED). The present study is based on secondary data covering a period of eleven years from 2000-01 to 2010-11. The analysis has been done through various techniques like ratio analysis, percentages, a.verage, charts etc. and for testing relationships Pearson Bivariate Correlation and ’T’ test has been applied. The study found that the federation relies more on equity as a source of finance but 10119 term loans are also being used from time to time. However, the degree of leverage is low. The equity and debt have their separate identity in the federation. The federation has high proportion of reserves & surplus so it can use debt capital in its structure without any difficulty.